1997
DOI: 10.1177/135910539700200403
|View full text |Cite
|
Sign up to set email alerts
|

Marriage, Intimate Support and Depression during Pregnancy

Abstract: We examined the influence of stress, intimate support and marital status on postpartum depression among 189 African American and European American, inner-city women. We selected women in three common categories: (1) married, (2) cohabitating with partner, and (3) romantically involved, but not cohabitating. Women were interviewed on two occasions during pregnancy and seven to nine weeks following delivery. Women who were not married and did not live with their partner reported less intimacy with their partner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
4
10
0
1
Order By: Relevance
“…Consistently, the findings of previous studies pointed out the importance of marital quality and adjustment as being significant associates of alleviated postpartum depression (Beck, 2001;Johanson, Chapman, Murray, Johnson, & Cox, 2000;Kumar & Robson, 1984;Misri et al, 2000;Righetti-Veltema et al, 1998). Besides the quality of the marriage it was reported that marriage or cohabitation reduced women's depression level as compared to the women who were not married and did not cohabitate (Gallagher, Hobfoll, Ritter, & Lavin, 1997). Thus a potential cause for postpartum depression may be the stress of marital maladjustment, but still it may be the other way around, that is, depression symptoms of these women may have contributed to marital distress.…”
Section: Discussionsupporting
confidence: 61%
“…Consistently, the findings of previous studies pointed out the importance of marital quality and adjustment as being significant associates of alleviated postpartum depression (Beck, 2001;Johanson, Chapman, Murray, Johnson, & Cox, 2000;Kumar & Robson, 1984;Misri et al, 2000;Righetti-Veltema et al, 1998). Besides the quality of the marriage it was reported that marriage or cohabitation reduced women's depression level as compared to the women who were not married and did not cohabitate (Gallagher, Hobfoll, Ritter, & Lavin, 1997). Thus a potential cause for postpartum depression may be the stress of marital maladjustment, but still it may be the other way around, that is, depression symptoms of these women may have contributed to marital distress.…”
Section: Discussionsupporting
confidence: 61%
“…Minors were allowed to participate with their assent and their guardians' informed consent. We excluded cohabitating women because we have found them to be more similar to married than single women and our focus was on single women (Gallagher, Hobfoll, Ritter, & Lavin, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…This finding is not always consistent across studies. One study found that for some married women, depressive symptoms do not appear to significantly affect their perception of intimate partner support after the birth of a child, even after controlling for initial levels of depressive symptoms (Gallagher, Hobfoll, Ritter, & Lavin, ). Given that most of the research finds that depressive symptoms are negatively associated with marital intimacy, we hypothesized that greater depressive symptoms would be associated concurrently with lower marital intimacy and with decreasing trajectories of marital intimacy (H8).…”
mentioning
confidence: 99%